The impact of economic globalization on the shadow economy in Egypt - Mohammad Reza Farzanegan; Mai Hassan (Philipps-University Marburg, School of Business and Economics, 2017)
This study examines the economic globalization and the shadow economy nexus in Egypt. Using time series data from 1976 to 2013, the impulse response analysis shows that the response of the shadow economy in Egypt to positive shocks in economic globalization is negative and statistically significant for the first three years following the shock. This finding is obtained by controlling for several intermediary channels in globalization-shadow economy nexus such as education, government spending, industrial production, and labor force participation. Our results show the importance of promoting economic globalization by reducing the costs of doing business and trade in dealing with sizable shadow economy in Egypt.
Keywords: 330; Shadow economy; Globalization; VAR model; Impulse responses; Egypt